Biomass Production and Rooting Behaviour of Eucalyptus tereticornis Sm. on Deep Soils and Riverbed Bouldery Lands of Doon Valley, India - Dhyani, S. K.; Puri, D. N.; Narain, P. (Indian Forester, 1996)
Above and below ground biomass production was estimated for Eucalyptus tereticornis Sm. Stands growing on deep textured soils and riverbed bouldery lands of Doon Valley. Above ground biomass production was 23.30 t ha-1 On the deep soils and 20.83 t ha-1 On the riverbed lands, while below ground production on these two sites was 7.51 t ha-1 and 11.04 t ha-1 Respectively. On the deep soils, 8.7% of total stand dry matter production was in fine roots, in contrast to over 26% on the riverbed lands. However, the difference in total biomass production between the two sites was small (1.06 t ha-1 ). The root characteristics viz., depth, number, lateral spread, weight and percentage roots in soils at the two sites were studied. It was observed that the development of the main root is largely dependent on soil type. In deep heavy textured soil, Eucalyptus developed a sparsely branched and deeply penetrating root system, while in riverbed bouldery lands a more compact intensively branched root system was recorded. In riverbed bouldery lands due to presence of impediments, coiling of roots was observed. A relationship between vertical root length and total root length to be known as "Coiling Factor" was established to compare coiling of roots under different soil working depths.